PENGARUH PILIHAN AUDITOR EKSTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gastriani, Ovi Prina; Sholihah, Mar'atus; Rosalina, Amanda; Sari, Nur Fajar Aprilia; Rismawati, Ria; Fajardini, Ridhani Anita (Gapenas Publisher, 2024)
This study aims to determine the effect of auditor choice, in this case Big-4 and Non-Big-4 Affiliated Auditors, on the Financial Reporting Quality in Banking Companies listed on the Indonesia Stock Exchange. The dependent variable in this study is Financial Reporting Quality with the proxy of Discretionary Accruals which are estimated using the Cross-Sectional Modified Jones Model. Meanwhile, the Independent Variable uses Big-4 or Non-Big-4 Auditor Choices. Hypothesis testing was carried out using Multiple Linear Regression analysis in 43 banking companies for 6 (six) years, namely 2016 – 2021. The test results show that the auditor choice has a negative effect on discretionary accruals. Thus, the auditor choice has an influence on the quality of financial statements.